2018
DOI: 10.3178/jjshwr.31.451
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo and Perspectives of Flood Runoff Analysis for Urban Watersheds

Abstract: This paper outlines the current status of flood runoff analysis for urban watersheds and presents its future prospects. First, I will describe the urban flood disaster, then briefly review the history of the runoff models before explaining the current state of application of flood runoff models for urban watersheds. Next, storage function models as the lumped conceptual model are outlined, and the urban storage function (USF) model is explained. Then, the necessity of a detailed distributed physical model in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Since then, along with the rapid development of computer and IT technology, the analysis of flood runoff in urban watersheds has been improved in several respects. Data collection by, e.g., satellites and radar is a significant advancement, as is the advancement of GIS technology [69]. Furthermore, a range of new methods based on, e.g., optimization methods, network theory, and AI, have been applied to flood runoff analysis and modeling.…”
Section: Brief History On Urban Runoff Modeling In Japanmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, along with the rapid development of computer and IT technology, the analysis of flood runoff in urban watersheds has been improved in several respects. Data collection by, e.g., satellites and radar is a significant advancement, as is the advancement of GIS technology [69]. Furthermore, a range of new methods based on, e.g., optimization methods, network theory, and AI, have been applied to flood runoff analysis and modeling.…”
Section: Brief History On Urban Runoff Modeling In Japanmentioning
confidence: 99%
“…Baba et al [22] and Hoshi et al [84] developed an SF model that directly uses the observed rainfall and runoff to solve the problems associated with the estimation of direct runoff. The proposal of a model concept that does not require the separation of baseflow is groundbreaking [69].…”
Section: Conventional Sf Modelsmentioning
confidence: 99%
See 1 more Smart Citation